2013
DOI: 10.1259/bjr.20120180
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlation of a new practical MRI method for assessing central lumbar spinal stenosis

Abstract: Objective: To evaluate interobserver agreement and determine whether a new MRI grading system agrees with symptoms and neurological signs. Methods:We examined 160 patients (72 males and 88 females; mean age 57 years) who underwent MRI of the lumbar spine at our institution and were evaluated by two musculoskeletal radiologists. The presence and grade of central lumbar spinal stenosis (CLSS) at L3-4, L4-5 and L5-S1 were assessed according to a new grading system, the Lee system. The results were correlated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 10 publications
2
25
0
2
Order By: Relevance
“…LCSS results from a combination of pathogenic factors, including a decrease in the area of the cauda equina, hypertrophy of ligamentum flavum, loss of intervertebral disk height, and hypertrophy of the facet joints [14]. LFS results from posterolateral osteophytes from the vertebral endplates, which protrude into the foramen along with a herniated disk or a laterally bulging annulus fibrosus.…”
Section: Discussionmentioning
confidence: 99%
“…LCSS results from a combination of pathogenic factors, including a decrease in the area of the cauda equina, hypertrophy of ligamentum flavum, loss of intervertebral disk height, and hypertrophy of the facet joints [14]. LFS results from posterolateral osteophytes from the vertebral endplates, which protrude into the foramen along with a herniated disk or a laterally bulging annulus fibrosus.…”
Section: Discussionmentioning
confidence: 99%
“…The overall percentage agreements were also calculated. Agreement was rated as follows: kappa value interpretations were poor (κ < 0.1), slight (0.1 ≤ κ ≤ 0.2), fair (0.2 < κ ≤ 0.4), moderate (0.4 < κ ≤ 0.6), substantial (0.6 < κ ≤ 0.8), and nearly perfect (0.8 < κ ≤ 1.0) ( 19 21 ). Among the various guidelines for interpreting ICCs, we adapted a scale that was introduced in previous literature: ICC values of less than 0.40 indicate poor reproducibility, values of 0.40-0.75 indicate fair to good reproducibility, and values greater than 0.75 indicate excellent reproducibility ( 20 22 ).…”
Section: Methodsmentioning
confidence: 99%
“… 10 , 11 LSSS results from multiple pathogenic risk factors, including a decrease in the area of the cauda equina, hypertrophy of LF, loss of intervertebral disk height and hypertrophy of the facet joints. 12 Several studies investigated the association between LF, dural sac area and spinal canal area on MRI and the signs and symptoms of LSSS. Park et al 13 reported that the LF is significantly thinner in patients with intervertebral disc herniation than in those with LSSS.…”
Section: Discussionmentioning
confidence: 99%